Pengaruh Profitabilitas, Likuiditas, dan Ukuran Perusahaan Terhadap Pengungkapan Islamic Sosial Reporting pada Bank Umum Syariah di Indonesia - Gaja, Hamzah Fansuri (Tauhidinomics: Journal of Islamic Banking and Economics, 2025)
This study aims to analyze the effect of Profitability (ROA), Liquidity (FDR), and Company Size (SIZE) on Islamic Social Reporting (ISR) Disclosure on BUS in Indonesia. ROA in this study is proxied through the Financial Performance Ratio, FDR is proxied through the FDR Ratio with third party funds, SIZE is proxied through Nominal Total Asset, and ISR Disclosure is proxied through the Islamic Social Reporting Index scoring. The data in this study were obtained from the official BUS website, and OJK. The sample used is 10 BUSs that publish annual financial reports for the period 2018-2022. The sampling method in this study was purposive sampling method. The data analysis method used in this study was panel data regression analysis using EViews 12 software. The results of this study indicate that partially the ROA and FDR variables do not affect ISR while the Size variable affects ISR, while simultaneously, the ROA, FDR and Size variables affect ISR disclosure at Islamic Commercial Banks in Indonesia. Keywords:ROA, FDR, SIZE, dan ISR.